Melatonin, a natural antioxidant therapy in spinal cord injury - Xie, Lei; Wu, Hang; Huang, Xiaohong; Yu, Tengbo (Frontiers in Cell and Developmental Biology, 2023)
Spinal cord injury (SCI) is a sudden onset of disruption to the spinal neural tissue, leading to loss of motor control and sensory function of the body. Oxidative stress is considered a hallmark in SCI followed by a series of events, including inflammation and cellular apoptosis. Melatonin was originally discovered as a hormone produced by the pineal gland. The subcellular localization of melatonin has been identified in mitochondria, exhibiting specific onsite protection to excess mitochondrial reactive oxygen species and working as an antioxidant in diseases. The recent discovery regarding the molecular basis of ligand selectivity for melatonin receptors and the constant efforts on finding synthetic melatonin alternatives have drawn researchers’ attention back to melatonin. This review outlines the application of melatonin in SCI, including 1) the relationship between the melatonin rhythm and SCI in clinic; 2) the neuroprotective role of melatonin in experimental traumatic and ischemia/reperfusion SCI, i.e., exhibiting anti-oxidative, anti-inflammatory, and anti-apoptosis effects, facilitating the integrity of the blood–spinal cord barrier, ameliorating edema, preventing neural death, reducing scar formation, and promoting axon regeneration and neuroplasticity; 3) protecting gut microbiota and peripheral organs; 4) synergizing with drugs, rehabilitation training, stem cell therapy, and biomedical material engineering; and 5) the potential side effects. This comprehensive review provides new insights on melatonin as a natural antioxidant therapy in facilitating rehabilitation in SCI.